The Translational Role of Animal Models for Estrogen-Related Functional Bladder Outlet Obstruction and Prostatic Inflammation - Santti Risto; Yatkin Emrah; Bernoulli Jenni; Streng Tomi (MDPI, 2022)
The prevalence of LUTS and prostatic diseases increases with age both in humans and companion animals, suggesting that a common underlying cause of these conditions may be age-associated alterations in the balance of sex hormones. The symptoms are present with different and variable micturition dysfunctions and can be assigned to different clinical conditions including bladder outlet obstruction (BOO). LUTS may also be linked to chronic non-bacterial prostatitis/chronic pelvic pain syndrome (CP/CPPS), but the relationship between these conditions is unknown. This review summarizes the preclinical data that supports a role for excessive estrogen action in the development of obstructive voiding and nonbacterial prostatic inflammation. Preclinical studies that are emphasized in this review have unequivocally indicated that estrogens can induce functional and structural changes resembling those seen in human diseases. Recognizing excessive estrogen action as a possible hormonal basis for the effects observed at multiple sites in the LUT may inspire the development of innovative treatment options for human and animal patients with LUTS associated with functional BOO and CP/CPPS.